PENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY, REPETITION (AIR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VB SDN 13 PEKANBARU - Efri Yunita; Gustimal Witri; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the fact that is found in the class VB SDN 13 Pekanbaru, which shows the results of learning of mathematics is still relatively low. Formulation the problem is this research is : “Does the implementation of Auditory, Intellectualy, Repetition (AIR) model can improving results of learning of mathematics students of SDN 13 Pekanbaru?”. This research aims to improving results of learning of mathematics students of SDN 13 Pekanbaru with implementation Auditory, Intellectualy, Repetition (AIR) model. The hypothesis of this study is that if the implementation of Auditory, Intellectualy, Repetition (AIR) model, can improving results of learning of mathematics students of SDN 13 Pekanbaru. This study was conducted in SDN 13 Pekanbaru in March 2016. This from is research is classroom action research (PTK) are planned as much as two cycle. The subjects were students of class VB SDN 13 Pekanbaru academic year 2015/2016 which amounted to 31 people consisting of 13 men and 18 women. Based on the results of research of teacher activity sheet seen rising each meeting. At the first meeting of the first cycle of 78,85%, the second meeting of the first cycle of 84,62%, at the fourth meeting of the second cycle of 92,31%, and the fifth meeting of the second cycle of 96,15%. Student activity observation sheet also increased at every meeting. At the first meeting of the first cycle of 73,08%, the second meeting of the first cycle of 86,54%, at the fourth meeting of the second cycle of 92,31%, and the fifth meeting of the second cycle of 94,23%. Mastery learning outcomes to repeat at first cycle increased 19,35% from the base score of 38,71% to 58,06%. In the second cycle increased by 25,81% to 83,87%. The average value in the base score 60,48, UH then the first cycle to 68,87 with an increase of 13,87%. Where as the second cycle of the average value of UH becomes 80,16 with an increase of 32,54%. So that research result are consistent with the hypothesis.Key words : Auditory, Intellectualy, Repetition (AIR) model, results of learning of mathematics